THE EFFECTS OF PUZZLE THERAPY ON REDUCING PSYCHOLOGICAL DISTRESS IN PRESCHOOL CHILDREN DURING HOSPITALIZATION - Putri Minas Sari; Milya Novera; Siti Aisyah Nur; Anggra Trisna Ajani; Debby Shintania; Reska Handayani; Rika Novariza; Mariza Elvira (Universitas Negeri Padang, 2024)
Hospitalization is a treatment performed in a hospital and can cause trauma and stress to patients who have recently been hospitalized. This is an experimental research with a quasi-experimental design and a pre-test- post-test approach. The population in this study were 62 cases using a purposive sampling technique. The results showed that the average level of anxiety before giving puzzle therapy was 4.94, the lowest score was 4 and the highest was 6. The average level of anxiety after giving puzzle therapy was 2.6 with the lowest score being 1 and the highest being 3. The results of the statistical test obtained a p value of 0.001, so there was an effect of giving puzzle play therapy on the level of anxiety in preschoolers (4- 5 years) during hospitalization. It is suggested that the hospital can provide health information about the benefits of playing puzzle therapy to the community as a way to reduce anxiety levels in children in patients without side effects